ANALISIS KEMAMPUAN VISUAL SPASIAL SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA BERSTANDAR PISA KONTEN SHAPE AND SPACE DITINJAU DARI LEVEL BERPIKIR GEOMETRI VAN HIELE - Ambarwati, A; Setiawan, Toto Bara; Yudianto, Erfan (Department of Mathematics Education , University of Jember, 2018)
This study was purposed to describe the students’ spatial visual ability in solving PISA standard math questions in Shape and Space content viewed from van Hiele's level of geometrical thinking. The research participants were 7 students who fulfilled each level of van Hiele's geometrical thinking starting from level 0 to level 3 in class XI IA 4 Glagah 1 Public Senior High School. Data collection methods were test and interviews. Based on data analysis, the results of the study show that students who are on level 3 van Hiele geometry levels, on levels between 2-3, and level 2 meet all characteristics of visual abilities. Meanwhile, students who are on levels between 1-2, level 1, levels between 0-1, and level 0 do not all meet the characteristics of spatial visual abilities. Characteristics of students' spatial visual abilities in imagination are the most dominant characteristics (most fulfilled) among the others, while the use of concepts (conceptualization) and using several ideas to find new ways are the most difficult characteristics to fulfill. Keywords: PISA standard math questions with Shape and Space content, van Hiele's level of geometrical thinking, spatial visual abilities.